2004
DOI: 10.1271/bbb.68.1875
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior of Fowl Feather Keratin

Abstract: Differential scanning calorimetry (DSC) was applied to elucidate the thermal behavior of fowl feather keratins (barbs, rachis, and calamus) with different morphological features. The DSC curves exhibited a clear and relatively large endothermic peak at about 110-160 degrees C in the wet condition. A considerable decrease in transition temperature with urea and its helical structure content estimated by Fourier transform infrared spectroscopy (FT-IR), and the disappearance of one of the diffraction peaks with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 17 publications
5
22
0
Order By: Relevance
“…They showed that the denaturation temperatures of -conglycinin and glycinin almost linearly increased from about 72 C to 102 C and from about 89 C to 129 C, respectively, as peak values evaluated by differential scanning calorimetry with a decreasing level of moisture. However, the other studies [5][6][7][8][9] did not show a linear increase in denaturation temperature with decreasing water content, and may have indicated a much higher denaturation temperature than the results reported by Sheard et al…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…They showed that the denaturation temperatures of -conglycinin and glycinin almost linearly increased from about 72 C to 102 C and from about 89 C to 129 C, respectively, as peak values evaluated by differential scanning calorimetry with a decreasing level of moisture. However, the other studies [5][6][7][8][9] did not show a linear increase in denaturation temperature with decreasing water content, and may have indicated a much higher denaturation temperature than the results reported by Sheard et al…”
mentioning
confidence: 70%
“…DSC for the SPI, -conglycinin, and glycinin preparations was carried out to determine the thermal denaturation from 25 C to 230 C at a heating rate of 5 K/min by using an SSC-5020 DSC-6100 instrument (SII Nanotechnologies; Tokyo, Japan) as described by Takahashi et al 13) A silver sample capsule (70 ml) was pretreated at 250 C for 20 min to prevent any exothermal effect from the capsule at around 170 C. 9) In the case of measurement with a wet sample, about 55 mg of a 10% dispersion in a 0.03 M Tris-HCl buffer at pH 8.0 was put into the capsule, while about 10 mg of the sorbed waterconditioned sample was put into the capsule for measuring the denaturation behavior of a dry sample. Three measurements were performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoothing was accomplished with the 11-point Savisky-Golay function, and the secondary structural contents were estimated from the peak area of the second-derivative spectrum according to the method previously described. 20) The peaks in the wavelength range of 1,600-1,700 cm À1 were generally assigned according to the results of Dong et al 21) and Beer et al, 22) , unordered. However, the major peak at 1,653 cm À1 was assigned in this experiment to an unordered structure, because sericin had a random coil structure.…”
Section: Measurement Ofmentioning
confidence: 99%
“…Keratins are made up two main subunits such as alpha and beta keratins which composed various amino acids [5]. The feathers are mainly composed of beta-keratin [6,7]. The investigation spotlights on degradation of the keratin containing chicken feathers by the bacterial strains of B. thuringiensis serovar israelensis (Bti) and Bacillus sphaericus (Bs) which are helpful in the production of endotoxins to destroy the mosquito larvae.…”
mentioning
confidence: 99%